A comprehensive investigation of computational fluid dynamics (CFD) wind flow simulation with a 3D building model - Ridzuan, Nurfairunnajiha (Prince of Songkla University, 2023)
The buildings can influence wind flow, while a better wind flow in a city will improve the air quality for the sustainable development of the urbanites. At present, Computational Fluid Dynamics (CFD) is commonly used for wind flow simulation. However, CFD simulation is able to focus only on a certain height of a building. Hence, the 3D building model Level of Details (LoD) plays a vital role in the simulation. As regards the 3D building model standard, CityGML standard provides different LoD such as LoD1.0, LoD1.1, LoD1.2, LoD1.3, LoD2.0, LoD2.1, LoD2.2, LoD2.3, LoD3.0, LoD3.1, LoD3.2 and LoD3.3. Thus, this study aimed to overcome this problem by determining the best 3D building model’s LOD for CFD wind movement simulation. This study ran CFD simulation experiments on each stated LoD using the same 3D model building. Several important points (locations) at the building were selected and analysed to obtain the best wind velocity analysis for the LoDs. Through such analysis, LoD3.1 was selected as the model that fulfils the minimum requirements to have the best CFD wind flow simulation. This research can help future planning of cities towards realizing sustainable city development by taking into account the factors affecting wind movement in the city.